2020
DOI: 10.1007/s13311-019-00772-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Melanocortin 1 Receptor Attenuates Early Brain Injury in a Rat Model of Subarachnoid Hemorrhage viathe Suppression of Neuroinflammation through AMPK/TBK1/NF-κB Pathway in Rats

Abstract: Neuroinflammation plays a vital role in early brain injury (EBI) following subarachnoid hemorrhage (SAH). The hypothesis of this study was that activation of melanocortin 1 receptor (MC1R) with BMS-470539 attenuates EBI by suppression of neuroinflammation after SAH. We utilized BMS-470539, MSG-606, and MRT-68601 to verify the neuroprotective effects of MC1R. We evaluated brain water content, short-term and long-term neurobehavior after SAH. Western blotting and immunofluorescence staining were utilized to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 42 publications
7
31
1
Order By: Relevance
“…Based on the evidence above, we further investigated the role of AMPK in C-176-mediated anti-inflammatory effects after SAH. Consistent with the previous study [28], an increased ratio of p-AMPK/AMPK after SAH was noted in this study. And we found that C-176 further promoted the phosphorylation of AMPK, which can be explained by the elimination of the negative impact of TBK1 on AMPK as reported [32].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the evidence above, we further investigated the role of AMPK in C-176-mediated anti-inflammatory effects after SAH. Consistent with the previous study [28], an increased ratio of p-AMPK/AMPK after SAH was noted in this study. And we found that C-176 further promoted the phosphorylation of AMPK, which can be explained by the elimination of the negative impact of TBK1 on AMPK as reported [32].…”
Section: Discussionsupporting
confidence: 93%
“…The frozen brain slides used for Nissl staining and hematoxylin and eosin (HE) staining were prepared in the same way as those used to immunofluorescence staining. Nissl staining was conducted to demonstrate the number of normal neuron in cortex and hippocampus as previously reported [28]. The frozen brain slides were immersed with 0.5% cresyl violet (Sigma-Aldrich, St. Louis, MO, USA) solution and dehydrated with 100% alcohol.…”
Section: Nissl Staining and Hematoxylin And Eosin Stainingmentioning
confidence: 99%
“…In the present study, an increase in AMPK phosphorylation was observed after Bak administration. Besides, the upregulation of AMPK phosphorylation occurs after SAH in the present study, which has also been reported previously (Osuka et al, 2009;Xu et al, 2019;Xu et al, 2020). In our opinion, this phenomenon may be caused by the compensation mechanism during which the self-protecting signal pathways have been activated to tolerate the stress.…”
Section: Discussionsupporting
confidence: 89%
“…TBK1/NF-κB signaling pathway contributed to inflammatory response [ 32 , 43 , 44 ]. To further explore the underlying molecular mechanism, the gain- and loss-of-function studies were conducted in L02 cells through infection with either Ad-shSIKE to suppress SIKE expression or Ad-SIKE to over-express SIKE ( Fig.…”
Section: Resultsmentioning
confidence: 99%